Performance of Motorcycle Fueled with Pertalite‒LDPE Pyrolytic Oil Blendings - Thoharudin, Thoharudin; Santosa, Tito Hadji Agung; Sukmana, Rifky Adji (Universitas Muhammadiyah Yogyakarta, 2024)
Plastic use has expanded substantially, and its waste is primarily disposed of in landfills, which further harm ecosystems owing to inadequate waste management. Pyrolysis, which converts plastic waste into liquid fuel, is one of the potential chemical recycling alternatives for plastic. The purpose of this study is to determine the viability of using pyrolytic oil from an LDPE grocery bag as an alternative fuel for a four-stroke spark ignition motorcycle engine. The LDPE grocery bag was pyrolyzed at 500 oC at a heating rate of 3 oC/min, and the condensed pyrolytic vapor's characteristics were determined. Torque, power, and fuel consumption were investigated using a four-stroke spark ignition motorbike powered by pertalite‒LDPE pyrolytic oil blends. The results reveal that the properties of LDPE pyrolytic oil and pertalite were considerably different; hence, when the blending fuel was applied to the motorcycle, the engine torque and power decreased at low engine speed (2000‒3500 rpm), about equal at medium speed (3500‒5500 rpm), and increased at high engine speed (5500‒8500 rpm). Furthermore, the greater blending fuel greatly reduced fuel usage due to the high viscosity of the LDPE pyrolytic oil.